Ehlers–Danlos syndrome, classical type. Issue 1 (13th February 2017) - Bowen, Jessica M.; Sobey, Glenda J.; Burrows, Nigel P.; Colombi, Marina; Lavallee, Mark E.; Malfait, Fransiska; Francomano, Clair A.
Abstract : Classical EDS is a heritable disorder of connective tissue. Patients are affected with joint hypermobility, skin hyperextensibilty, and skin fragility leading to atrophic scarring and significant bruising. These clinical features suggest consideration of the diagnosis which then needs to be confirmed, preferably by genetic testing. The most recent criteria for the diagnosis of EDS were devised in Villefranche in 1997. [Beighton et al. (1998); Am J Med Genet 77:31‐37]. The aims set out in the Villefranche Criteria were: to enable diagnostic uniformity for clinical and research purposes, to understand the natural history of each subtype of EDS, to inform management and genetic counselling, and to identify potential areas of research. The authors recognized that the criteria would need updating, but viewed the Villefranche nosology as a good starting point. Since 1997, there have been major advances in the molecular understanding of classical EDS. Previous question marks over genetic heterogeneity have been largely surpassed by evidence that abnormalities in type V collagen are the cause. Advances in molecular testing have made it possible to identify the causative mutation in the majority of patients. This has aided the further clarification of this diagnosis. The aim of this literature review is to summarize the current knowledge and highlight areas for future research. © 2017 Wiley Periodicals, Inc.